E-COMMERCE WEBSITES PERFORMANCE AND STABILITY ANALYSIS - Sadovska, Tatjana; Sadovskis, Dmitrijs; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The goal of the work is to make performance and stability analysis for the most popular e-commerce websites in Latvia, evaluate metrics and suggest improvements. Analysis result should provide necessary information for companies’ owners to increase conversion rate and reduce bounce rate.